PENGARUH PROFITABILITAS, LEVERAGE, DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE (Studi pada perusahaan perbankan yang terdaftar di BEI tahun 2017-2019) - Akhmad Darmawan; Bagas Akbar Dwi Pangestu Rimbawan; Dwi Vina Rahmawati; Bima Cinintya Pratama (LPPM University 17 Agustus 1945 Samarinda, 2020)
The purpose of the empirical study is to examine and analyze the effect of Profitability, Leverage, and Audit Quality on tax avoidance with Company Size as a moderating variable. The empirical research sample is a banking company listed on the Indonesia Stock Exchange (IDX) in 2017-2019 with 22 company samples. This study uses multiple regression analysis as hypothesis testing. The results of empirical research are (1) Profitability has a significant negative effect on tax avoidance, (2) Leverage has no effect on tax avoidance, (3) Audit quality has no effect on tax avoidance.